Endoscopic submucosal tunnel dissection for large esophageal neoplastic lesions - Pioche, Mathieu; Mais, Laetitia; Guillaud, Olivier; Hervieu, Valérie; Saurin, Jean-Christophe; Ponchon, Thierry; Lepilliez, Vincent (Endoscopy, 2013)
Background and study aim: Endoscopic submucosal dissection (ESD) is recommended for en bloc R0 resection of superficial esophageal neoplasms larger than 20 mm, but is high risk and time-consuming. In the tunnel technique, incisions at the lower and upper lesion edges are joined by a submucosal tunnel and then lateral incisions are made. The mucosa is thereby easily separated from the muscular layer. We report our experience of esophageal tunnel ESD.Patients and methods: We retrospectively reviewed all consecutive esophageal tunnel ESDs performed at our unit between January 1 2010 and January 11 2013. Lesions were superficial esophageal neoplasms, UT1N0 at EUS. Results: 11 patients underwent tunnel ESD (nine squamous cell carcinomas, two adenocarcinomas). Mean dissected surface area was 13.25 cm². Mean procedure duration was 76.7 minutes. All 11 resections were en bloc and 9 /11 were R0. Complications were one subcutaneous emphysema with spontaneous resolution, and stenosis in 4 /11 patients (36.4 %) with resolution after 1 – 5 dilations.Conclusion: Tunnel ESD of superficial esophageal neoplasms is an interesting option, seeming to be faster and more effective than standard ESD, without higher morbidity.